Mit tehet a nők egészségéért egy rózsaszínű szalag és egy elhivatott védőnő? A dunaújvárosi járási népegészségügyi osztály kommunikációs tevékenységének bemutatása - Dózsáné Sasvári Ildikó Anna (2016)
The thesis deals with the communication activity of the National Public Health and Medi-cal Officer Service (hereinafter ÁNTSZ with Hungarian initials) with reference to the health development activity of one of its regional organizational units i.e. the District Pub-lic Health Department of Dunaújváros. The external communication activity of the ÁNTSZ and its regional organizations has been changed in the recent years primarily due to the acceleration of information flow and the need of population for knowledge. The current leaders and representatives of for-merly invisible and faceless authorities regularly inform the population on the actual public health issues by means of the media. The thesis presents the structure of the public health organization, its relationships, line of its duties and the legal background determining its activity. The place of the district public health department of Dunaújváros in the current public administration system to-gether with the rules of communication relating to the organization and its said unit are al-so described. The separation of professional management from the functional one resulted in surplus activities in the communication activity of the regional organizations. The thesis presents the organizational communication of the district public health department of Dunaújváros in connection with two cases. The first one is the organization and arrangement of the event called walk of Dunaújváros against mammary cancer while the other one is the introduction of uterine cervix screening performed by welfare workers in the field of competence of the department. The thesis presents the public health indices relating to mammary cancer and uterine cervix cancer and the objectives of the relevant health development programs. Following the collection of the available documentation and the experiences relating to the organization and arrangement, the communication activity of the public health department is detailed and analyzed in connection with two health development programs.. The thesis evaluates the success of communication performed by the organizational unit on the basis of its results, efficiency and potency. Then, the fields where the devel-opment and changes are in any case justified are emphasized. In order to implement the health development programs with a proper efficiency the conscious organization of the internal organizational communication is also required. The successful communication in the field of health development results in health-conscious behaviour and participation in screening tests on a larger scale on the part of the population. These factors improve the public health indices on a long term.